Comparison of teleportation and walking in virtual reality in a declarative learning task - Rihs, Michael; Steuri, Rahel A.; Aeschlimann, Sarah A.; Mast, Fred W.; Dobricki, Martin (Frontiers in Virtual Reality, 2024)
Virtual reality (VR) offers new possibilities for learning in educational settings by navigating through large 3D virtual environments. When designing VR-based learning applications, developers have to decide between different locomotion techniques to navigate through VR. Since physical activity and walking have been shown to enhance learning, physical walking in VR should increase learning compared to locomotion techniques without physical activity. In this study, we examined if learners who are able to walk freely in VR differ regarding their declarative knowledge acquisition from learners who are teleported in VR. Learning outcomes did not differ between these two conditions, neither immediately after learning in VR nor after a one-day delay. Also, participants' sense of presence in the virtual environment did not differ between the two conditions. These findings suggest that both teleportation and walking are suitable for declarative knowledge acquisition in VR, and that teleportation may be sufficient enough.